Common mosses of the Northeast and Appalachians - McKnight, Karl B. (Princeton field guides., 2013)
This is the first book to help general readers recognize 200 common mosses of the Northeast and the Appalachian Mountains. With just this field guide, a hand lens, and a spray bottle--no microscopes necessary--readers will be able to identify and name many of the common species of mosses growing in the region's backyards, parks, forests, wetlands, and mountains. At the heart of this guide is an innovative, color-tabbed system that helps readers pick out small groups of similar species. Illustrated identification keys, colorful habitat and leaf photos, more than 600 detailed line drawings, a.